2013
DOI: 10.1016/j.psyneuen.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Early interactions with mother and peers independently build adult social skills and shape BDNF and oxytocin receptor brain levels

Abstract: The early social environment has a profound impact on developmental trajectories. Although an impoverished early environment can undermine the acquisition of appropriate social skills, the specific role played by the different components of an individual’s early environment in building social competencies has not been fully elucidated. Here we setup an asynchronous communal nesting paradigm in mice to disentangle the influence of maternal care and early peer interactions on adult social behavior and neural sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
125
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 65 publications
4
125
0
Order By: Relevance
“…Here, we have shown that laboratory mice reliably form linear and stable dominance hierarchies after being put together within 48e96 h. Importantly, each mouse within a hierarchy had a unique and distinct social rank and responded consistently to more and less dominant members of their network with appropriate behaviour indicative of high sociocognitive competence (Branchi et al, 2013;Taborsky & Oliveira, 2012). There also was variability between groups in how unevenly power was distributed within the hierarchy.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Here, we have shown that laboratory mice reliably form linear and stable dominance hierarchies after being put together within 48e96 h. Importantly, each mouse within a hierarchy had a unique and distinct social rank and responded consistently to more and less dominant members of their network with appropriate behaviour indicative of high sociocognitive competence (Branchi et al, 2013;Taborsky & Oliveira, 2012). There also was variability between groups in how unevenly power was distributed within the hierarchy.…”
Section: Resultsmentioning
confidence: 85%
“…personality variables like risk taking or boldness, or social competence) may be just as important as or more important than aggression in determining social status in mice (David, Auclair, & C ezilly, 2011;Fox, Ladage, Roth, & IIPravosudov, 2009;Hsu, Earley, & Wolf, 2006;Taborsky & Oliveira, 2012). Second, this finding suggests that standard laboratory tests of social dominance using animals tested in pairs in tasks such as the tube-test (van den Berg et al, 2015;Wang et al, 2011), food competition (Benner et al, 2014;de Jong, Korosi, Harris, Perea-Rodriguez, & Saltzman, 2012;Timmer, Cordero, Sevelinges, & Sandi, 2011) or aggression (Bales & Carter, 2003;Branchi et al, 2013) tests, are not necessarily robust indicators of an individual's ability to ascend a social hierarchy when living within a large social group comprising a number of complex social relationships.…”
Section: Formation and Maintenance Of Social Hierarchiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mother-infant relationship is therefore critical to proper social development; however, research also demonstrates the importance of the larger social milieu (17)(18)(19)(20). For example, a recent study in mice found that early interactions with mothers and peers independently shape adult behavior (21). Likewise, some negative impacts of maternal deprivation are attenuated in macaques that are raised in peer groups (22).…”
mentioning
confidence: 99%
“…While this may be suggested as attractive approach when embedded in neurobiological research it may on the other hand threat studies in which stress is unwanted and could cause artefacts. With regard to a long-range perspective a healthy life relies upon early experiences and adaptations can be made adequately [48,49]. With disadvantaged early conditions like postulated by our CM paradigm there is an increased risk of stress and maladaptation.…”
Section: Resultsmentioning
confidence: 99%